Habib Husein Ja'far's Self Presentation Strategy in Digital Da'wah on Youtube - Muhammad Revi Hari Prajanto; Rama Kertamukti (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2023)
The self-presentation strategy is necessary in delivering dakwah (Islamic preaching) materials to make them appealing to the youth as the target audience. This study aims to interpret the selfpresentation performed by Habib Husein Ja'far through the YouTube channel Jeda Nulis. This research employed a qualitative descriptive approach to provide an overview of how Habib Husein Ja'far adjusted the theme of da'wah and self-presentation according to his segmentation on Youtube. The findings of the research indicate that Habib Husein Ja'far addressed many problems that tend to be experienced by young people with a relaxed and humorous style but serious in his response. Moreover, his self-presentation portrays him as a tolerant preacher who is close to young people. This research contributes knowledge to the self-presentation of preachers on YouTube in order to be able to creatively convey da'wah in accordance with the challenges of the current era. Strategi presentasi diri diperlukan dalam menyampaikan materi dakwah agar dapat diterima anak muda sebagai target dakwah. Penelitian ini bertujuan untuk menafsirkan presentasi diri yang dilakukan oleh Habib Husein Ja’far melalui channel Youtube Jeda Nulis. Penelitian ini dilakukan dengan pendekatan deskriptif kualitatif. Penelitian ini menganalisis video dakwah Habib Husein Ja'far untuk memberikan gambaran bagaimana Habib Husein Ja'far menyesuaikan tema dakwah dan presentasi diri sesuai dengan segmentasinya di Youtube. Hasil penelitian menunjukkan bahwa Habib Husein Ja'far banyak mengangkat permasalahan yang cenderung dialami oleh anak muda dengan gaya santai dan penuh candaan tapi serius dalam menjawabnya. Sedangkan presentasi diri yang dihadirkan oleh Habib Husein Ja’far adalah pendakwah yang toleran dan dekat dengan anak muda. Hasil penelitian ini memberikan pengetahuan dalam presentasi diri pendakwah di Youtube agar dapat menyampaikan dakwah secara kreatif sesuai dengan tantangan zamannya.